The Utilization of Ocimum sanctum L. Essential Oil for Antimicrobial Edible Packaging and Its Application for Aloe Vera Dodol - Pramono Putro Utomo; Hidayati Hidayati (Balai Riset dan Standardisasi Industri Pontianak, 2013)
Aloe vera dodol is a traditional food of West Kalimantan that has short shelf life because of its microbial activity. Antimicrobial edible packaging could be used to maintain the quality of packaged food product actively.The purpose of this study is to prolong the shelf life of food products using antimicrobial edible packaging from durian peel and basil (Ocimum sanctum L.) essential oil. The research was conducted through 4 phases,i.e. the extraction of pectin from durian peel, basil essential oil distillation, Aspergillus flavus inhibition assay, and antimicrobial edible coating production incorporated with Ocimum sanctum L. essential oil. The results showed that pectin extracted from durian peel at pH 4.5 could give yield of 5.9% with a clear coat (Colourless).The concentration of Ocimum sanctum L. essential oil by 0.6% could inhibit the growth of Aspergillus flavus and prolong the shelf life when applied as an antimicrobial ingredient in edible coating.